Sorghum plant characteristics and yield and its interaction with mycorrhizal fungi under irrigation and rainfed conditions - Díaz Franco Arturo; Peña del Río María de los Ángeles (Revista Mexicana de Ciencias Agrícolas, 2018)
Sorghum response (‘DK- 345’) to six native strains of experimental arbuscular mycorrhizal fungi (AMF) [3 (Funneliformis mossae), 20 (Gigaspora albida), 32 (F. mossae), 35 (F. mossae), 39 (F. mossae), 55 (Gigaspora sp.)] was compared to mycorrhizal INIFAP (Rhizophagus intraradices) and non-inoculated check under irrigated and rainfed conditions. The chlorophyll index (SPAD) was measured in three stages (f lag leaf, f lowering and end of flowering), in addition to plant height, biomass and grain yield. In flag leaf, chlorophyll index variations among AMFstrainsandhumidityconditionswereobserved.AMF did not inf luence the chlorophyll index during f lowering. Although at the end of f lowering, outstanding strains were 55 and mycorrhizal INIFAP. Plant height was similar among AMF, but 16.5 cm higher in irrigation. Biomass was similar among the AMF but higher than control. The highest grain yield in the two humidity conditions was obtained with strain 55 and mycorrhizal INIFAP. This study showed the comparative potential of native AMF strains in sorghum.